Activation of Anti-Tumor Immune Response and Reduction of Regulatory T Cells with Mycobacterium indicus pranii (MIP) Therapy in Tumor Bearing Mice - Ahmad, Faiz (Public Library of Science, 2011)
BACKGROUND: Role of immune system in protecting the host from cancer is well established. Growing cancer however subverts immune response towards Th2 type and escape from antitumor mechanism of the host. Activation of both innate and Th1 type response is crucial for host antitumor activity. In our previous study it was found, that Mycobacterium indicus pranii (MIP) also known as M. w induces Th1 type response and activates macrophages in animal model of tuberculosis. Hence, we studied the immunotherapeutic potential of MIP in mouse tumor model and the underlying mechanisms for its antitumor activity. METHODOLOGY AND PRINCIPAL FINDINGS: Tumors were implanted by injecting B16F10 melanoma cells subcutaneously into C57BL/6 mice. Using the optimized dose and treatment regimes, anti-tumor efficacy of heat killed MIP was evaluated. In MIP treated group, tumor appeared in only 50–60% of mice, tumor growth was delayed and tumor volume was less as compared to control. MIP mediated immune activation was analysed in the tumor microenvironment, tumor draining lymph node and spleen. Induction of Th1 response and higher infiltration of immune cells in the tumor microenvironment was observed in MIP treated mice. A large fraction of these immune cells were in activated state as confirmed by phenotypic and functional analysis. Interestingly, percentage of Treg cells in the tumor milieu of treated mice was less. We also evaluated efficacy of MIP along with chemotherapy and found a better response as compared to chemotherapy alone. CONCLUSION: MIP therapy is effective in protecting mice from tumor. It activates the immune cells, increases their infiltration in tumor, and abrogates tumor mediated immune suppression.